Cone-beam computed tomographic evaluation of dimensional hard tissue changes following alveolar ridge preservation with leucocyte and platelet-rich fibrin techniques: a pilot study - Passos da Silva, Natalia; Carlos Costa da Silva, Joao; Freitas, André; Margarida Cruzoé Rebello, Iêda; Yang, Ruijia; Wang, Tao; Zhao, Rusin; Nogueira, Getulio (Brazilian Dental Science, 2022)
Objective: This study evaluated the effect of leucocyte and platelet-rich fibrin (L-PRF) techniques used in alveolarridge preservation on dimensional hard tissue changes of the alveolar ridge assessed using cone-beam computedtomography (CBCT) scans. Material and Methods: Elective alveolar ridge preservation surgeries were performedon seven systemically healthy patients who underwent single posterior tooth extraction. Patients were randomlytreated with PRF mixed with a commercial bone xenograft (n = 3) or PRF plug (n = 4). CBCT scans weretaken immediately after tooth extraction and then four months later, just before implant surgery. Dimensionalalterations in socket height (SH), socket area (SA) and socket volume (SV) were evaluated on CBCT scans bypercentage differences before and after treatments. Results: Sockets treated with PRF plus bone xenograft had atendency to maintain alveolar bone dimensions over time (SH= 11.22% to 82.74%, SA= 1.84% to 48.91% andSV= 9.11% to 203.62%), while sockets treated only with PRF plug technique presented only a modest increasein height (SH= 1.47% to 11.11%) but greater alveolar ridge resorption confirmed by a decrease in socket areaand volume dimensions (SA= 0.21% to -24.09% SV= 8.53% to -54.12%). Conclusion: Within the limitationsof this study, the maintenance of alveolar socket dimensions was observed when PRF was associated with axenograft. However, the loss of alveolar ridge dimensions was not entirely prevented by PRF treatment alone.KEYWORDSAlveolar bone loss; Bone substitutes; Cone-beam computed tomography; Platelet-rich fibrin; Tooth socket.